An anthropologist in parallel structure - Noelle Molé Liston (Anuac, 2016)
The essay examines the parallels between Molé Liston’s studies on labor and precarity in Italy and the United States’ anthropology job market. Probing the way economic shift reshaped the field of anthropology of Europe in the late 2000s, the piece explores how the neoliberalization of the American academy increased the value in studying the hardships and daily lives of non-western populations in Europe.